Megamarsupial extinction : the carrying capacity argument - Webb, R. Esmée
An ancient and contentious debate in prehistory (Owen 1846; Lyell 1863) asks if the megafauna of newly colonized worlds was exterminated by human hunting, or whether other factors, such as changing climate, were decisive. Debate on this issue remains lively in Australia, because its harsh environments surely posed problems for very large mammals. A starting-point for this fresh look at megafaunal extinction was Flannery's (1994) adoption of the 'blitzkrieg' hypothesis, in which humanly caused kill-off was so rapid it left no decisive archaeological traces.